Investigation of 7-benzylidenenaltrexone derivatives as a novel structural antitrichomonal lead compound. Issue 21 (1st November 2015) - Kutsumura, Noriki; Nakajima, Ryo; Koyama, Yasuaki; Miyata, Yoshiyuki; Saitoh, Tsuyoshi; Yamamoto, Naoshi; Iwata, Satoshi; Fujii, Hideaki; Nagase, Hiroshi
Graphical abstract